Amniotic membrane-mesenchymal stromal cells secreted factors and extracellular vesicle-miRNAs: Anti-inflammatory and regenerative features for musculoskeletal tissues. (3rd March 2021) - Ragni, Enrico; Papait, Andrea; Perucca Orfei, Carlotta; Silini, Antonietta Rosa; Colombini, Alessandra; Viganò, Marco; Libonati, Francesca; Parolini, Ornella; Girolamo, Laura
Abstract: Human amniotic membrane-derived mesenchymal stromal cells (hAMSCs) are easily obtained in large quantities and free from ethical concerns. Promising therapeutic results for both hAMSCs and their secreted factors (secretome) were described by several in vitro and preclinical studies, often for treatment of orthopedic disorders such as osteoarthritis (OA) and tendinopathy. For clinical translation of the hAMSC secretome as cell-free therapy, a detailed characterization of hAMSC-secreted factors is mandatory. Herein, we tested the presence of 200 secreted factors and 754 miRNAs in extracellular vesicles (EVs). Thirty-seven cytokines/chemokines were identified at varying abundance, some of which involved in both chemotaxis and homeostasis of inflammatory cells and in positive remodeling of extracellular matrix, often damaged in tendinopathy and OA. We also found 336 EV-miRNAs, 51 of which accounted for more than 95% of the genetic message. A focused analysis based on miRNAs related to OA and tendinopathy showed that most abundant EV-miRNAs are teno- and chondro-protective, able to induce M2 macrophage polarization, inhibit inflammatory T cells, and promote Treg. Functional analysis on IL-1β treated tenocytes and chondrocytes resulted in downregulation of inflammation-associated genes. Overall, presence of key regulatory molecules and miRNAs explain the promising therapeutic results of hAMSCs and their secretome for treatment of musculoskeletal conditions and are a groundwork for similar studies in other pathologies. Furthermore, identified molecules will pave the way for future studies aimed at more sharply predicting disease-targeted clinical efficacy, as well as setting up potency and release assays to fingerprint clinical-grade batches of whole secretome or purified components. Abstract : The secretome from human amniotic membrane-derived mesenchymal stromal cells offers tremendous potential for treatment of musculoskeletal disorders. Combined analysis of soluble factors and extracellular vesicle-miRNAs show their teno-/chondro-protective features, as well as ability to induce M2 macrophage polarization, inhibit inflammatory T cells, and promote Treg. The fingerprint of key regulatory molecules will define the potency of future off-the-shelf and cell-free regenerative therapies.